New data on small lampreys of the genus Lethenteron (Petromyzontidae) of the Tom River, a typical habitat of the Siberian brook lamprey Lethenteron kessleri - Interesova, Elena A.; Babkina, Irina B.; Romanov, Vladimir I.; Pozdnyak, I. V.; Davletshina, G. I.; Trifonov, Vladimir A. (Journal of Ichthyology, 2022)
The article presents data of morphological and molecular-genetic analyzes of small lampreys from the Tom River, a typical habitat of the Siberian brook lamprey Lethenteron kessleri (Anikin, 1905), as well as of one specimen of a large lamprey caught in the same period of the year in the Ob River. All studied specimens are similar in the structure of the dental apparatus to lampreys of the upper Ob tributaries and the upper Irtysh basin, and also correspond to the characteristics of Lethenteron camtschaticum. They have one haplotype of the mitochondrial cytochrome oxidase c subunit I gene, previously described for lampreys from the Ob River basin and the rivers of the White Sea basin. Currently, there is no reason to consider small lampreys of the Tom River as a valid species Lethenteron kessleri.